2019
DOI: 10.1186/s12954-019-0301-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescribed use of methadone and buprenorphine prior to opioid substitution treatment: lifetime prevalence, motives, and drug sources among people with opioid dependence in five Swedish cities

Abstract: Background Opioid substitution treatment (OST) with methadone or buprenorphine is the most effective means of treating opioid dependence. If these substances are used by people who are not undergoing OST, they can however carry serious risks. This article examines the lifetime prevalence, motives, and drug sources for such use, as well as geographical differences in these variables. Methods Structured interviews were conducted with 411 patients from 11 OST clinics in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…However, such non-prescribed use also involves substantial risks, as has been shown by this and other studies [15,17,36,59]. Since non-prescribed use is often driven by pseudotherapeutic motives [62], increased access to OST might decrease the illicit demand for these substances [60,61].…”
Section: Differences Between Deaths Caused By the Various Substances mentioning
confidence: 72%
“…However, such non-prescribed use also involves substantial risks, as has been shown by this and other studies [15,17,36,59]. Since non-prescribed use is often driven by pseudotherapeutic motives [62], increased access to OST might decrease the illicit demand for these substances [60,61].…”
Section: Differences Between Deaths Caused By the Various Substances mentioning
confidence: 72%
“…As diversion of methadone is illegal and often leads to exclusion from OAT in Sweden, it is not surprising that police reports and other information do not capture this possible source. The majority of methadone prescriptions in Sweden are for SUD treatment [36] and a recent study in Sweden based on qualitative interviews of patients in OAT found a life‐time prevalence of non‐prescribed methadone use of 88% [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, concerns are still raised regarding the risks of misuse and diversion (Kenney, Anderson, Bailey, & Stein, 2017; Lin, Lofwall, Walsh, Gordon, & Knudsen, 2018; Mund & Stith, 2018). However, in many cases diversion is committed by opioid-dependent individuals to self-medicate in accordance with the legal purpose of buprenorphine (Bazazi, Yokell, Fu, Rich, & Zaller, 2011; Johnson & Richert, 2019). Additionally, non-medical use of buprenorphine is safer than methadone (Lee, Klein-Schwartz, Welsh, & Doyon, 2013).…”
Section: Buprenorphinementioning
confidence: 99%